Kegiatan Pengabdian Masyarakat Terhadap Deteksi Dini Gangguan Perilaku, Emosional, dan Psikososial di Sekolah Dasar Negeri Caringin - Agustina Agustina; Wahyuni Wahyuni; Asoka Dhananjaya; Dennis Zefanya Budiman; Laura Bernadeth Manik; Salim Santoso; Erick Erick; Alexander Halim Santoso (Institut Teknologi dan Bisnis Semarang, 2024)
Parents and other mental health stakeholders are becoming more concerned about emotional and behavioral disorders (EBPs) in teenagers. These issues, which typically arise in infancy or adolescence, have an impact on relationships, academic achievement, and other areas. They may even persist into adulthood as mental health disorders (MHD). Using the Pediatric Symptom Checklist (PSC-17) questionnaire, the risk of behavioral, emotional, and psychosocial disorders was assessed in this activity. It is anticipated that early detection—made possible by instruments like the PSC-17—will avert long-term issues brought on by behavioral, emotional, and psychological illnesses.